SISTEM CERDAS PENDIAGNOSIS KECANDUAN INTERNET YANG MENGGUNAKAN SISTEM PAKAR RUNUT MUNDUR - Iksan, Nur; Yani, Achmad; Manaf, Abdi; Ismail; Panessai, Ismail Yusuf (ITP Press, 2023)
Starting with COVID19, almost everyone around the world uses the internet, even to the worrying stage, namely internet addiction. Several studies report that the level of addiction to using the internet network is getting higher even though COVID19 has subsided. Teenagers have not been able to choose useful internet connection activities and they are more prone to experiencing bad influences from the social environment. To overcome this they need support from psychologists so they can prevent and diagnose early before they become sufferers of severe internet addiction. But on the other hand, the number of psychologists who can help is still very limited, especially in small towns. In addition, economic factors and limited time for parents to accompany their children to visit psychologists are the main obstacles. Therefore it is necessary to find a solution that can overcome the limitations and barriers to adolescents in obtaining services from a psychologist. One solution to this problem is to build an expert system that can work as a psychologist. The purpose of this research is to build an expert system application for diagnosing internet addiction using the backward chaining method. Internet addiction level is categorized in low, medium and high. System testing is carried out using black box testing which allows experts to obtain a set of output conditions that will carry out all functional requirements of the program. This test shows that the inout and output data has been running as expected.